2016
DOI: 10.1186/s12968-016-0289-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance patterns of biopsy proven cardiac involvement in systemic sclerosis

Abstract: BackgroundTo determine morphological and functional cardiovascular magnetic resonance (CMR) patterns in histopathologically confirmed myocardial involvement in patients with systemic sclerosis (SSc).MethodsTwenty patients (6 females; mean age 41 ± 11 years) with histopathologically proven cardiac involvement in SSc in the years 2008–2016 were retrospectively evaluated. Morphological, functional and late gadolinium enhancement (LGE) images were acquired in standard angulations at 1.5 T CMR. Pathologies were cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 39 publications
(43 reference statements)
0
20
2
3
Order By: Relevance
“…This evaluation has not the same quantitative value as T 1 mapping and does not replace T 1 mapping but gives an overview over potential diffuse myocardial contrast agent uptake. We have not found pathologically diffuse contrast agent uptake in our study cohort, whereas these findings are common in cardiac involvement of systemic and storage diseases (18).…”
Section: Cmr Resultscontrasting
confidence: 69%
“…This evaluation has not the same quantitative value as T 1 mapping and does not replace T 1 mapping but gives an overview over potential diffuse myocardial contrast agent uptake. We have not found pathologically diffuse contrast agent uptake in our study cohort, whereas these findings are common in cardiac involvement of systemic and storage diseases (18).…”
Section: Cmr Resultscontrasting
confidence: 69%
“…We found a different prevalence of patients with isolated nT1 elongation (30%, in most cases with concomitant increase in the T2 value) and combined nT1/ECV increase (42.5%). These tissue signal abnormalities could express a combination of low grade inflammation (increase of nT1 and T2) and diffuse myocardial fibrosis (expanded ECV) [ 8 , 30 ], that might precede the contractile impairment occurring at late stage of SSc-related cardiopathy[ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent large study, diastolic dysfunction was more predominant than systolic, and several factors such as primary heart disease, vascular lung disease, and PAH contributed to it (82). Also, other studies have shown reduced RV ejection fraction and RV dilatation (77), further enhancing the notion of a primary RV impairment in SSc. Altered RV ejection fraction has been reported as a poor prognostic factor in PAH and other clinical conditions, such as heart failure, reduced LVEF, or ischemic cardiomyopathy (85).…”
Section: Assessment Of Right Ventricular Involvementmentioning
confidence: 97%